2019
DOI: 10.2166/wp.2019.238
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling gendered practices in the public water sector in Nepal

Abstract: Despite decades of gender mainstreaming in the water sector, a wide gap between policy commitments and outcomes remains. This study aims at offering a fresh perspective on such policy gaps, by analysing how gendered discourses, institutions and professional culture contribute to policy gaps. We rely on a conceptual framework originally developed for analysing strategic change, which is used to analyse gender in the public water sector in Nepal. Our analysis relies on a review of national water policies and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Despite the multifaceted nature of water management and gender inequality, development interventions tend to be limited and enacted in policy silos . For a more socially justified water management, develoment actions have to address at least three issues together: policy discourses, organizational components, and institutions of the implementing organizations (Shrestha & Clement, 2019). One such example related to the importance of enhancing organizational capacity and changing institutions is that the local government staff responsible for water management in the municipal area seemed unaware of the burden of water scarcity faced by women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the multifaceted nature of water management and gender inequality, development interventions tend to be limited and enacted in policy silos . For a more socially justified water management, develoment actions have to address at least three issues together: policy discourses, organizational components, and institutions of the implementing organizations (Shrestha & Clement, 2019). One such example related to the importance of enhancing organizational capacity and changing institutions is that the local government staff responsible for water management in the municipal area seemed unaware of the burden of water scarcity faced by women.…”
Section: Discussionmentioning
confidence: 99%
“…Policy texts too often miss to mention “women” at all in water management laws and regulations, with limited chances of consideration of women's interests while implementing these policies (Udas & Zwarteveen, 2010; Zwarteveen & Meinzen‐Dick, 2001). Even when there are decentralized policies with the provision of women's representation (which varies by country), what is lacking is a genuine engagement of women in the formulation and implementation of water sector policies (Shrestha & Clement, 2019; Shrestha et al., 2019). Earlier studies on gender and participation show that despite their presence in the decision‐making bodies, many women could not express themselves as they felt inhibited in expressing their views in front of village elders (men) due to lack of confidence (Meinzen‐Dick & Zwarteveen, 1998; Regmi & Fawcett, 1999; Satyal et al., 2020).…”
Section: Gender Inequality In Water and Developmentmentioning
confidence: 99%
“…Coupled with systemic discrimination in the labour market by Indian and local higher cast thekedars (labour contractors), the almost complete lack of Musahar participation in the tourist and conservation economy around CNP is not that surprising. Such socially differentiated stream of benefits by ethnicity and caste is not surprising in this context as women's empowerment programmes have also had uneven impacts because of local social geographies and patriarchy (Leder et al, 2017;Shrestha and Clement, 2019).…”
Section: Contested Conservation Waterscapes In Nepalmentioning
confidence: 99%
“…The success of women's involvement has varied for many reasons, including inadequate project design, cultural and social constraints, as well as policy and legal constraints (Tennyson, 2002). Past watershed projects around the globe (Leder et al, 2017;Shrestha and Clement, 2019;Udas and Zwarteveen, 2010) revealed that gender issues have been a part of watershed management projects. However, the extent to which these issues were addressed has varied, and the recommended changes have not always been made.…”
mentioning
confidence: 99%
“…Men are perceived to be responsible for production and management of farms or small businesses, even though women are very much involved in these enterprises. Despite women's significant role in water use and household management, women's needs and uses of water are often not represented in water resource management policies or projects (Varua et al, 2018;Leder et al, 2017Leder et al, , 2019Udas and Zwarteveen, 2010;Shrestha and Clement, 2019;Suhardiman et al, 2015).…”
mentioning
confidence: 99%